2016
DOI: 10.1158/1078-0432.ccr-16-0452
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Causes of Pituitary Adenomas

Abstract: Recently, a number of novel genetic alterations have been identified that predispose individuals to pituitary adenomas. Clinically relevant pituitary adenomas are relatively common, present in 0.1% of the general population. They are mostly benign monoclonal neoplasms that arise from any of the five hormone-secreting cell types of the anterior lobe of the pituitary gland, and cause disease due to hormonal alterations and local space-occupying effects. The pathomechanism of pituitary adenomas includes alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 131 publications
(165 reference statements)
0
74
0
12
Order By: Relevance
“…Thus, we performed whole‐genome sequencing on matched tumor and normal blood samples from a patient with aggressive prolactinoma with severe invasion and surrounding bone destruction, aiming to identify somatic genetic alterations. We found that prolactinomas have a low mutational burden, as reflected by their benign nature (Caimari & Korbonits, ; Song et al, ). In addition, we identified novel somatic mutations in the POU domain, class 6, transcription factor 2 ( POU6F2 ) gene (OMIM, *609062, NM_001166018.2: c. 839 C>T; c. 875A>G).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we performed whole‐genome sequencing on matched tumor and normal blood samples from a patient with aggressive prolactinoma with severe invasion and surrounding bone destruction, aiming to identify somatic genetic alterations. We found that prolactinomas have a low mutational burden, as reflected by their benign nature (Caimari & Korbonits, ; Song et al, ). In addition, we identified novel somatic mutations in the POU domain, class 6, transcription factor 2 ( POU6F2 ) gene (OMIM, *609062, NM_001166018.2: c. 839 C>T; c. 875A>G).…”
Section: Introductionmentioning
confidence: 99%
“…Pituitary abnormalities, including both pituitary adenoma and lymphocytic hypophysitis, have been rarely described in patients with NF1, although recognition is increasing 3. Attention to the suprasellar region, in addition to the brain tissue, and orbits, on brain imaging of patients with NF1 is advised.…”
Section: Discussionmentioning
confidence: 99%
“…gynaecomastia, may develop without detectable hormone imbalance leading the investigators to the conclusion endocrine diagnostics appear to be unnecessary in these patients [99]. Furthermore, the putative causal relation between the rare case for primary pituitary adenoma and NF1 is presently unclear [100]. Table 20 (Tab.…”
Section: Discussionmentioning
confidence: 99%